ASSESSMENT THE SAFETY POLICY MANAGEMENT FOR BUILDING CONSTRUCTION COMPANIES IN JORDAN - Alubaid, Faidhi Abdulrahman Salman (Journal of Applied Engineering Science, 2020)
In Jordan the building construction industry is considered to be one of the most significant industries in terms of contributing to economy, and also in terms of its impact on health and safety of the working people. Construction industry is so important for both sides the socially and economically. At the same time, the construction industry, is also known to be the most hazardous. Therefor it is essential to investigate and assess the factors effecting safety policy of building construction companies in Jordan, and identifying the level of attention in applying the safety related factors. This research identifies seven of these factors that have the greatest impact to arise.  Subsequently, a questionnaire survey was presented into 64 question. The questionnaire survey was distributed to 179 (1st, 2nd and 3rd degree) companies which provided by Jordanian construction contractors association. Statistical analysis was carried out to 145 responding companies by employing the (SPSS) program. Data related to safety policy management were analyzed and discussed in details.